Incobotulinumtoxina A diluída em solução de gluconato de zinco para rugas faciais : ensaio clínico randomizado - Ferreira, Leonardo Oliveira (2017)
Introduction: Botulinum toxin is a zinc-dependent metalloprotease and promotes cleavage of the receptor responsible for botulinum toxin type A with consequent paralysis at the neuromuscular junction. In addition to blocking the release of acetylcholine, it inhibits the local release of pain-related neuropeptides. Although more recognized in aesthetics, it is indicated in the treatment of several disorders. Objective: To evaluate the efficacy and duration of the effect of botulinum toxin type A (incobotuliniumtoxin A) applied to the frontal muscle of women, being reconstituted in zinc gluconate compared to dilution in physiological solution. Methods: This is a prospective, double-blind study. The sample size was 48 females, over 50 years of age and divided into two groups, being calculated using the G-Power program to verify the association between variables. For this purpose an effect of 0.5, a power of the test of 80% and a level of confidence of 95% were used. The comparison between the two groups was performed by the Mann-Whitney test. The non-parametric test was chosen because the variables had no normal distribution (Kolmogorov-Smirnov p> 0.05). The various moments were compared by the Kruskall-Wallis test. In the control group, Incobotuliniumtoxin A flasks (100 U) were diluted in 2 mL of 0.9% sodium chloride physiological solution. In the case group, it was diluted with 2 mL of a 0.02% zinc gluconate solution. Participants were monitored using the Merz-Esthetics validated scale of resting and moving frontal lines and documented by means of digital photography, the results of which were analyzed by Wilcoxon's non-parametric test to compare the frontal lines before and after the application. To characterize the groups, descriptive statistics methods were used as frequencies and percentages for categorical variables and median, minimum and maximum for quantitative variables. The chi-square and Manny-Whitney tests were used to verify the homogeneity of the groups in relation to the clinical variables. Results: The results showed that there is no relationship between race, ethnicity, smoking and sunscreen use with the toxin effect in the two groups. For the variables age and amount weekly zinc intake the Manny-Whitney test result indicated that there was no significant difference in the groups. In the control group, at 14 weeks of application, there was a 66% reduction of the effects in patients with resting frontal wrinkles and a 75% reduction in the desired effect on movement. In the case group, after 14 weeks of application, there was a 100% reduction in effects in patients with resting frontal wrinkles and 75% in movement. Conclusion: The data identify that patients' life habits do not influence the final outcome of the procedure and that the duration of the effect is not related to the dilution of the product with a substance other than the classic dilution with physiological solution. However, the study showed that patients who ingest alcoholic beverages using Botulinum toxin diluted in 0.02% zinc gluconate seem to have better efficacy.